2013
DOI: 10.1088/0957-0233/24/12/125204
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the depletion beam focal spot using near-field scanning optical microscopy probes

Abstract: The submicron size doughnut shape focal spot, which is traditionally measured by scattering off a nanoparticle or a fluorescent bead, is measured for the first time by a near-field scanning optical microscopy (NSOM) fiber probe. Measurement results agree very well with calculations. This method offers superior repeatability, better control and is less time-consuming than the traditional method as the probes are mechanically protected by their insertion into fiber optic ferrules, which also greatly facilitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Furthermore, the Richard and Wolf formula is valid even for numerical aperture approaching one [24]. Using a microscope objective with NA = 0.85, the spatial profile of the focal spot predicted by the Richard and Wolf formula agreed very well with experimentally measured profile using a scanning NSOM probe [21].…”
Section: Image Plane Formulasupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the Richard and Wolf formula is valid even for numerical aperture approaching one [24]. Using a microscope objective with NA = 0.85, the spatial profile of the focal spot predicted by the Richard and Wolf formula agreed very well with experimentally measured profile using a scanning NSOM probe [21].…”
Section: Image Plane Formulasupporting
confidence: 65%
“…With formulas given above and the numerical aperture of the microscope objective and the input beam parameters specified, it is shown that the focal spot spatial profile agrees very well with the measured profile using a NSOM tip in the collection mode of operation [21] If the focal plane is to be shifted away from the origin of the particle, then simply make the following change in the expression for I 0 , I 1 , and I 2 :…”
Section: Appendixmentioning
confidence: 56%
See 1 more Smart Citation